2020
DOI: 10.1007/s00277-020-04251-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of EP300-ZNF384 fusion in patients with acute lymphoblastic leukemia using RNA fusion gene panel sequencing

Abstract: EP300-ZNF384 fusion is a rare recurrent cytogenetic abnormality associated with B cell acute lymphoblastic leukemia (B-ALL), which was rarely studied in Chinese patient cohort. Here, we used a customized RNA fusion gene panel to investigate gene fusions in 56 selected acute leukemia patients without conventional genetic abnormalities. Two EP300-ZNF384 fusion forms were detected in ten cases, which were in-frame fusions of EP300 exon 6 fused with exon 3 or 2 of ZNF384. The fusions led to the lack of most functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
(32 reference statements)
2
11
0
Order By: Relevance
“…Moreover, luciferase activity assay confirmed that miR-200c-3p directly targeted the Western blot showed that the expression of miR-200c-3p was negative correlated with target gene EP300. Previous studies suggested that EP300 may be involved in oncogenic processes in several different carcinomas including lung, prostate, laryngeal squamous cell cancer, breast cancer and leukemia [32][33][34][35][36]. These results suggested that miR-200c-3p played an antitumour role targeting EP300 in nephroblastoma.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, luciferase activity assay confirmed that miR-200c-3p directly targeted the Western blot showed that the expression of miR-200c-3p was negative correlated with target gene EP300. Previous studies suggested that EP300 may be involved in oncogenic processes in several different carcinomas including lung, prostate, laryngeal squamous cell cancer, breast cancer and leukemia [32][33][34][35][36]. These results suggested that miR-200c-3p played an antitumour role targeting EP300 in nephroblastoma.…”
Section: Discussionmentioning
confidence: 82%
“…3,10,11 However, some patients with EP300-ZNF384 also suffered relapses and were refractory to salvage chemotherapy (Supplementary Table 3). 5 Both patients reported here had weak expression of CD20 and therefore presented no target for anti-CD20 monoclonal antibody or CD20-targeted CAR T-cell therapy. As reported in most cases, exon 6 of EP300 was fused with exon 3 of ZNF384 in both cases.…”
Section: Dovepressmentioning
confidence: 85%
“…6 At present, only two EP300-ZNF384positive B-ALL patients have undergone CAR T-cell therapy; however, both patients died. 5 No details about the efficacy and safety of CAR T-cells for these patients were reported. Despite the high response rate of CD19 CAR T-cell therapy, approximately 50% of R/R B-ALL patients relapsed after CD19 CAR T-cell therapy, which is partially due to CD19 antigen loss.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…It encodes a zinc finger protein that functions as a transcription factor and regulates the expression of matrix metalloproteinases [ 3 ]. In ZNF384 -rearranged BCP-ALL, the breakpoints of ZNF384 are typically located in exons 2 and 3, which contain the entire ZNF384 protein that may be responsible for the characteristics of the immunophenotype [ 4 , 5 ]. Therefore, the presence of ZNF384 rearrangements should be a hallmark and the diagnostic criterion of a separate subtype of BCP-ALL since patients harboring such rearrangements have a distinctive immunophenotype.…”
Section: Introductionmentioning
confidence: 99%